Pengaruh Tax Expert, Intensitas Persediaan, Pertumbuhan Penjualan, Dan Konservatisme Akuntansi Terhadap Tax Avoidance - Frans Andita; Sri Handayani (Jurnal Riset Akuntansi Politala, 2026)
Taxes play a crucial role as the primary source of government revenue. However, conflicts of interest regarding tax obligations arise between the government and companies. On the one hand, the government seeks to maximize tax revenue as a source of national income, while on the other hand, companies aim to minimize their tax burden in order to maximize profits. This study aims to examine the effect of tax experts, inventory intensity, sales growth, and accounting conservatism on tax avoidance in the Basic Materials sector during the 2022–2024 period. This study employs a causal research design using secondary data consisting of 186 observations selected through purposive sampling. The sample includes companies that were consistently listed on the Indonesia Stock Exchange (IDX) throughout the study period. The data were analyzed using multiple linear regression analysis. The findings reveal that inventory intensity has a positive effect on tax avoidance, while sales growth has a negative effect on tax avoidance. Meanwhile, tax experts and accounting conservatism have no significant effect on tax avoidance. This study contributes to the literature by providing insights for companies in developing tax planning strategies that consider inventory intensity and sales growth, while also supporting the Theory of Planned Behavior in explaining managers' tax-related decision-making.